AKSESIBILITAS PELAYANAN TRANSPORTASI LAUT BAGI MASYARAKAT HINTERLAND KOTA BATAM (STUDI KASUS DI KECAMATAN BULANG) - Savitri, Egidia; Abbas, Azhar (LPPM Universitas Putera Batam, 2019)
Purpose this study to describe the accessibility of sea transportation services for the people Hinterland in Batam City. This study uses descriptive research method with qualitative approach. Data collection techniques are carried through observation, interviews, and documentation. Interviews were conducted to Head UPT Transportation Service, Private Boat Owner in the Bulang sub-district. This study was analyzed using the Dimension quality of public services, where accessibility is connecting how people obtain service marine transportation by seeing of service quality dimensions, are: 1) Reliability, to provide precisely and correctly, type of service has been promised community. 2) Responsiveness, awareness or desire to help and provide fast service to the community or willingness to help customers and carry out services sincerely. 3) Assurance, knowledge or insight, politeness, government, and respect for the community, as well level of attention ethics and morals in providing services. 4) Empathy, the willingness of government to approach providing protection, and trying find out the wants and needs of the community, characterized by the willingness to know wants and needs of consumers. 5) Tangiable, physical appearance, meaning the services provided are realized in of physical appearance such as buildings, equipment, and other facilities.